Research on SIM Card-Based Mobile Digital Signature and Authentication for Financial Services - Bo Hu; Binfeng Yan; Jianshu Qiu; Shuanghe Dong (Dianxin kexue)
With the development of smart phones and mobile internet，it is a trend that leveraging mobile devices to perform user authentication for cross industry application，such as electric bank. Traditional USB key based digital signature and authentication has been replaced by authentication based on mobile devices. Requirements for mobile digital signature and authentication method based on smart phones and SIM card were analyzed，architecture and service procedures for SIM card-based mobile digital signature and authentication were proposed.